Indicators for monitoring cataract surgery outcomes; evolution and importance - Khandekar, Rajiv; May, W; Alasbali, T (Nepalese Journal of Ophthalmology, 2015)
Cataract is one of the leading causes of blindness globally (Pascolini & Mariotti, 2012). Cataract surgery restores vision and is a cost-effective health intervention ranked second to the vaccination. In the ‘VISION 2020 -The Right to Sight’ initiative, cataract is given the highest priority so that member countries of the World Health Organization can eliminate avoidable blindness by the year 2020 (World Health Organization, 2007). From a public health perspective, the quantity and quality of cataract surgery is important. Hence, indicators to monitor cataract surgeries are both quantitative and qualitative. These indicators have changed along with the evolution of cataract services.